TREATMENT AND PROPHYLAXIS DIETETICS FOR OCCUPATIONAL DISEASES OF FIREFIGHTERS - Свідло, Карина; Цимбал, Богдан; Каролоп, Олена (SWorldJournal, 2025)
The paper examines the working conditions of firefighters and substantiates the role of therapeutic and preventive dietetics in reducing the risk of occupationally induced diseases. It is shown that firefighting is accompanied by exposure to a complex of